Operationalising the Deprivation of Liberty Safeguards (DoLS) in support of brain injury survivors – views from practice. Issue 4 (22nd June 2021) - Scott, Jade; Weatherhead, Stephen; Manthorpe, Jill
Abstract : Purpose: Deprivation of Liberty Safeguards (DoLS), as part of the Mental Capacity Act 2005 (DoLS, 2007), was established to provide a legal framework for decision-making in respect of adults who lack capacity to make decisions in relation to their care and residence in England and Wales. The purpose of this study was to explore the DoLS decision-making process from the perspectives of health and social care practitioners when working with individuals with an acquired brain injury (ABI). Design/methodology/approach: A total of 12 health and social care practitioners were interviewed in 2019–2020 about their experiences of using and making or supporting decisions in the DoLS framework with ABI survivors. Data were analysed, and a tentative explanation of variations in DoLS decision-making was developed. Findings: Three distinct approaches emerged capturing different decision-making styles (risk-averse, risk-balancing and risk-simplifying) which appeared to influence the outcome of DoLS assessments. A range of mediating factors seemed to account for the variability in these styles. The wider contextual challenges that impact upon practitioners' overall experiences and use of DoLS processes in their ABI practice were noted. Research limitations/implications: The findings highlight a need for changes in practice and policy in relation to how DoLS or similar processes are used in decision-making practice with ABI survivors and may be relevant to the implementation of the Liberty Protection Safeguards that are replacing the DoLS system. Originality/value: To the best of the authors' knowledge, this is the first study to explore accounts of DoLS decision-making practices in ABI service.